2013
DOI: 10.1017/s1355617713000568
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Defects Contribute to the Genesis of Closing-in in Alzheimer's Disease Patients

Abstract: Closing-in (CI) refers to copying drawings near to or superimposed on the original model, and is often observed in Alzheimer's disease (AD) patients. Contrasting hypotheses have been suggested to explain CI, but no prospective study has directly verified these interpretations. We evaluated the role of frontal/executive versus visuo-spatial impairments in a prospective sample of AD patients, and also explored whether different types of CI are related to specific neuropsychological tasks. We enrolled 64 AD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 32 publications
7
45
1
2
Order By: Relevance
“…With respect to dementia, one study found that the frequency of CI was greater in patients with dementia than in brain-damaged patients (Gainotti, 1972). This association between CI and dementia has been confirmed and specified in a number of large survey studies (Ambron et al, 2009a;2009b;De Lucia et al, 2013;Grossi et al, 2014;. Among the different forms of dementia, CI has been classically conceived as a common feature of AD (Ober et al, 1991;Rouleau et al, 1996;Spinnler and Della Sala, 1988) with estimated frequencies ranging from 38 to 77% (see Table 1).…”
Section: Anatomo-clinical Correlates Of CImentioning
confidence: 85%
“…With respect to dementia, one study found that the frequency of CI was greater in patients with dementia than in brain-damaged patients (Gainotti, 1972). This association between CI and dementia has been confirmed and specified in a number of large survey studies (Ambron et al, 2009a;2009b;De Lucia et al, 2013;Grossi et al, 2014;. Among the different forms of dementia, CI has been classically conceived as a common feature of AD (Ober et al, 1991;Rouleau et al, 1996;Spinnler and Della Sala, 1988) with estimated frequencies ranging from 38 to 77% (see Table 1).…”
Section: Anatomo-clinical Correlates Of CImentioning
confidence: 85%
“…However, this hypothesis specifically envisages strong correlations between CI and frontal/executive dysfunction, and foresees that CI can be triggered by high attention-demanding task conditions. Several converging pieces of evidence supported this account, since a significant correlation between CI and frontal/executive dysfunction has been reported in MCI [196], AD [191], VaD [25], and Parkinson's disease [189], and in such diseases copying geometrical figures in dual-task conditions enhanced CI [25,184,197]. A first attempt at identifying the neural correlates of CI in AD patients would point to bilateral orbito-frontal cortex as the area in which atrophy was significantly associated to presence of CI [198].…”
Section: Closing-inmentioning
confidence: 97%
“…For the Rey Figure, the same method was adopted, but in this case near-CI was classified not only when the copy was produced within the model's page, but also when the figure was copied within 10 mm from the upper edge of the response sheet (De Lucia et al, 2013). For the Rey Figure, the same method was adopted, but in this case near-CI was classified not only when the copy was produced within the model's page, but also when the figure was copied within 10 mm from the upper edge of the response sheet (De Lucia et al, 2013).…”
Section: Assessment Of Closing-inmentioning
confidence: 99%
“…Frontal/executive defects can also be associated to closingin (CI) in visuo-constructional copying tasks (Conson, Salzano, Manzo, Grossi, & Trojano, 2009;De Lucia, Grossi, Fasanaro, Carpi, & Trojano, 2013;De Lucia, Grossi, & Trojano, 2014), where patients reproduce drawings near to or superimposed on the original model (Mayer-Gross, 1935). CI has been often reported in AD (De Lucia et al, 2013, 2014Serra, Fadda, Perri, Caltagirone, & Carlesimo, 2010), but it occurs in patients affected by FTD too.…”
Section: Introductionmentioning
confidence: 99%